An exploration of the effects of information giving and information needs of women with newly diagnosed early‐stage breast cancer: A mixed‐method systematic review - Guanfa Zou; Alison Simons; Samantha Toland (Wiley, 2022)
Abstract Aim To review the information needs of women with newly diagnosed early‐stage breast cancer and the effects of information giving by measuring patient‐reported outcomes. Design A mixed‐method systematic review using PRISMA guidelines. Methods The major electronic nursing databases were searched from inception until 31 December 2019 using key terms. Included studies were assessed using the Crowes Critical Appraisal Tool. Results Four quantitative studies and two qualitative studies, comprising of 537 participants (age range from 25 to 98 years), were included for the ultimate qualitative synthesis of this review. There was high‐level evidence that demonstrated the prevalence of these groups of women's information needs and their improvement in fighting spirit and decrease in helplessness/hopelessness for information giving interventions; low‐level evidence of long‐term adjustment and well‐being improvement; and limited evidence indicating that inadequate information, including restricted information, too much information and conflicting information could cause some ramifications.